Evaluation of dentists' knowledge about management of patients with bleeding disorders in Kermanshah, Iran - Maryam Haghi; Marjan Haghi; Bijan Kaboudi; Sirous Nasiri; Asadolah Mohebi; Yasaman Mahmoudi Zangeneh (Isfahan University of Medical Sciences, 2013)
Introduction: Dentists must be aware of the impact of bleeding disorders on the management of their patients. The aim of this study was to determine dentists' knowledge about management of patients with bleeding disorders in Kermanshah, Iran. Materials and Methods: Ninety dentists were randomly selected for the purpose of this cross-sectional research from the public and private sectors in Kermanshah in 2012. The knowledge was evaluated by using a self-administrated questionnaire containing 11 questions about high-risk dental procedures for bleeding (11 scores) and 8 questions about coagulation tests (8 scores). Pearson's correlation coefficient and one-way ANOVA were used for evaluation of association between variables (α = 0.05).Results: The response rate was 88% (79 from 90 cases). The mean of total score of knowledge was 10.9 ± 3.2 out of maximum 19 scores; 63.3% of dentists had acceptable knowledge (knowledge score above 60% of maximum score). Approximately 40% of dentists scored lower than seven in the section on high-risk dental procedures for bleeding. Only 34% of dentists scored higher than 5 in the section on coagulation tests. There was a negative association between job experience and use of tests to control coagulation status (p value = 0.02). Conclusion: According to the results, dentists in Kermanshah have insufficient knowledge about bleeding disorders. Planning of educational courses for dentists is necessary in this respect. Key words: Blood coagulation tests, Dentists, Knowledge